Theoretical and experimental study of the multistage dynamic dehumidifier for enhanced thermal comfort conditions in a building. Issue 3 (4th May 2022) - Suranjan Salins, Sampath; Reddy, S.V. Kota; Kumar, Shiva
Abstract : In the present study, a mathematical model is constructed to simulate the heat and mass transfer process in a counterflow multistage reciprocating dehumidifier unit. Four packings are positioned at different positions where a camshaft mechanism controls their linear motion. Packings dip inside the Calcium Chloride desiccant instead of the conventional spray technique, improving the wettability and dehumidification effect. Theoretical and experimental results are compared. System performance is analyzed by varying the number of packing and performance parameters such as outlet temperature, specific humidity, moisture effectiveness, moisture removal rate, mass transfer coefficient and pressure change. Results indicated that the system gave maximum moisture effectiveness, moisture removal rate and mass transfer coefficient equal to 0.75, 2.21 g/s and 15.08 kg/m 2− s. Stage-wise evaluation of the performance shows that there is a significant improvement in the dehumidification performance by the addition of multiple stages.